Framing Kebijakan Pendidikan Islam dalam Media Massa: Analisis Konstruksi Wacana dan Implikasinya terhadap Persepsi Publik - Yosie Kristin Pandriyani; Wasehudin (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study aims to analyze the framing of Islamic education policy in the mass media and examine its implications for the formation of public perception. In the context of the development of digital information, mass media plays a strategic role in constructing social reality through the selection of issues, perspectives, and emphases. This study uses a qualitative approach with critical discourse analysis methods to examine news texts from several national mass media regarding Islamic education policy in Indonesia. Data were collected through documentation techniques on news articles published over a specific period, then analyzed using a framing model to identify narrative structures, highlighted actors, and underlying ideologies. The results show that mass media tend to frame Islamic education policy in various ways, ranging from normative and political to controversial perspectives, which indirectly influence public opinion and perception. This framing has implications for the formation of public understanding that is not always objective, but rather influenced by media interests and the socio-political context. Therefore, critical media literacy is needed so that the public can interpret information more wisely and proportionally.